A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

anonymous

  • 5 years ago

Find the unknown: (-5y-2)^2+11=18

  • This Question is Closed
  1. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    take -1 out from (-5y - 2)^2:

  2. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    (-1[5y+2])^2 = [5y+2]^2

  3. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    so now: [5y+2]^2 = 18 - 11 (move 11 to the right)

  4. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    (5y+2)^2 = 7 25y + 20y + 4 = 7

  5. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    move 7 to the left: 25y + 20y +4 -7 = 0 25y + 20y - 3 = 0

  6. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Now find discriminant: D = b^2 - 4ac, where b = 20, a = 25 and c = -3

  7. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    what did you do with the -1 after you factored it out?

  8. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Oh it was inside a square right, so: (-1[5y+2])^2 = (-1)^2 [5y+2]^2 = 1 * [5y+2]^2 = [5y+2]^2

  9. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Oh it was inside a square right, so: (-1[5y+2])^2 = (-1)^2 [5y+2]^2 = 1 * [5y+2]^2 = [5y+2]^2

  10. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    sorry for late response, i just keep crashing..

  11. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    no problem

  12. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    25y + 20y - 3 = 0 D = b^2 - 4ac, where b = 20, a = 25 and c = -3 D = 400 + 300 = 700

  13. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    i got it! thanks! :)

  14. bahrom7893
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    okay np.. can you please click on become a fan, thanks!

  15. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    sure!

  16. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...

23

  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.